“Disinformation Aims to Mislead; Misinformation Thrives in Ignorance”: Insights from Experts and Non-Experts in Greek-Speaking Cyprus - Loukia Taxitari; Thanos Sitistas; Eleni Gavriil (Social Sciences)
The article herein examines the multifaceted challenges of misinformation and disinformation in the media landscape, with a focus on strategies to enhance media literacy among adults. The primary objective of this study is to examine the prevalence, characteristics, and impact of disinformation and misinformation in media within the internet society, ultimately contributing to developing targeted educational programs and policy recommendations. To achieve this, a qualitative research design was carried out to explore the views and the broader societal experiences in media-related challenges. The research design utilized thematic analysis of data collected from focus groups and expert interviews, ensuring the representation of diverse perspectives. By focusing on the information landscape in Cyprus and Greece, the present article aims to address the unique local challenges and contribute to the literature gap. The findings reveal the critical importance of tailored educational programs and the cultivation of critical thinking skills in fostering media literacy and combating false information in an effort to put together in a unique study the various experiences, opinions, and needs of individuals who seek to navigate successfully in an information-rich world.